High-Risk Travel Abroad Overtook Low-Risk Travel from 1999 to 2004: Characterization and Trends in 2,622 Spanish Travelers - Valerio, Lluís; Martínez, Octavi; Sabrià, Miquel; Esteve, María; Urbiztondo, Luis; Roca, Carme (Journal of travel medicine, 2005)
Travel medicine in Spain is provided by a few specialized centers that do not come under the auspices of the main health system. Some kind of reform is required to avoid common summer collapses and postponements of the service. In contrast to other European countries, neither the exact role nor the responsibilities of general practitioners and primary health care in travel medicine are clearly defined. An observational study was performed with retrospective data concerning 2,622 travelers from 1999 to 2004. Although the study was performed at a third-level travel medicine center, continuous contact with and support to general practitioners was maintained throughout the period. International travel was a steadily increasing reality between 1999 and 2004 despite well-known tragic events involving world safety. The number of high-risk travels (53.4%) also increased and even overtook low-risk ones (46.6%). This trend was explained as the result of an increasing number of journeys to sub-Saharan Africa (14.9%) and those made by traveling immigrants (64.1% of those journeys), which represented a significantly higher proportion of high-risk travels compared with those made by autochthonous subjects (52.1%; p < .001). Moreover, traveling immigrants tend to consult more frequently in periods < 15 days prior to travel than do autochthonous travelers (p < .0001). A substantial number of highly vulnerable travelers, such as pregnant women, infants, elderly people, and immunosuppressed subjects, was found (1.8%). Low-risk travelers who could have been advised and vaccinated by general practitioners were 1,139 (43.4%). Given the increasing number of travelers undertaking high-risk travels abroad, any kind of reinforcement of travel medicine provision in Spain should be considered essential. General practitioners could attend to a significant proportion of low-risk travelers.